(untitled) (Journal of EAHIL, 2025)
We report briefly on the establishment of the Global Academy of Agriculture and Food Systems (GAAFS), a new interdisciplinary research group at the University of Edinburgh and how this required the library to identify and learn about additional search resources on top of those within our usual repertoire. We share examples of some of the resources which were found to be most useful for One Health and Planetary Health.